Spectral Characterization of Pigment from the No. 1 Cave, Kizil Cave-Temple Complex. (30th September 2019) - Liu, Liu; He, Jintao; Ye, Mei; Zhu, Zhanyun; Zhong, Qing; Yang, Junchang
Abstract : The Kizil Cave-Temple Complex has been registered as a World Heritage site and was formerly a part of Kucha—one of the most powerful and prosperous regions of ancient China. The No. 1 Cave is of great significance due to its three surviving clay sculptures. The mural paintings inside the cave are experiencing severe degradation. Scientific methods such as optical microscopy (OM), scanning electron microscopy combined with energy dispersive X-ray analysis (SEM-EDS), Raman spectroscopy, Fourier transform infrared spectroscopy (FTIR), and X-ray diffusion (XRD) were applied to analyze the pigments and organic coating used in the No. 1 Cave. The results show that paratacamite, gypsum, and lapis lazuli were used as the green, white, and blue pigments, respectively. Poly- n -butyl methacrylate (PBMA) was used as an organic coating of the blue pigment and has accelerated the aging of the mural paintings. This study shares insights into the materials and techniques employed and assesses the preservation status of the mural paintings, providing scientific support for protection and restoration schemes.